The zero lower bound on deposit rates, monetary policy and bank insolvency risk - Lorenz Driussi (Swiss National Bank, Study Center Gerzensee, 2025)
I develop a banking model with monopolistic competition to analyze the effect of reserve rate policy on bank insolvency risk, when banks are constrained by a zero lower bound on deposit rates. When binding, the lower bound compresses the solvency relevant deposit spread and causes it to be a function of the policy rate, which results in the policy rate affecting bank default. The policy rate has an impact through two separate effects: The direct effect increases default probability unambiguously as a lower policy rate decreases the deposit spread for every realization of credit risk. By contrast, the (indirect) risk effect may increase or decrease default probability depending on the hazard function of credit risk. The risk effect arises because banks endogenously adjust their solvency threshold in response to a policy rate change. This novel result suggests that in a low interest rate environment, the relationship between competition in the banking sector, monetary policy and financial stability cannot be isolated from the underlying credit risk distribution.
Keywords: D40; E43; E52; G21; 330; Zero lower bound; Reserve rate policy; Bank insolvency; Credit risk; Monti-Klein; Deposit spread